Coverage in the armenian historiography of the work of the rear of Soviet Armenia during the Great Ppatriotic War - Gasparyan, Volodya (History and Culture, 2023)
Not only the Armenian soldier made an outstanding contribution to the victory of the Great Patriotic War, but also the entire Armenian people. Owing to the daily heroic work of the workers of industry sector of Soviet Armenia, 30 new industrial enterprises were put into operation during the war years, and 300 new types of products were mastered by the industry, including 10 types of weapons. Owing to agricultural workers, plans to supply the front with bread, meat, butter, tobacco and drinks were fulfilled. The Armenian intelligentsia also provided significant assistance to the front, putting all their strength into the cause of victory. In this sense, coverage of the heroic labor of the workers of Soviet Armenia during the Great Patriotic War was one of the important issues of Armenian historiography. Over the past years, monographic and collective works devoted to the problem have been created, many articles have been published, a collection of documents and materials has been compiled, etc. However, this noble cause would be more beneficial if a general work was created in Russian and other languages that would familiarize a new generation of post-Soviet countries and the world community with the achievements of Armenian working circles in achieving victory in the Great Patriotic War and the achievements of Armenian historiography in the field of research of the issue.
Keywords: Great Patriotic War; Soviet Armenia; rear; front; agriculture; industry; ammunition; food; enterprises; culture